2021
DOI: 10.1186/s40510-021-00381-5
|View full text |Cite
|
Sign up to set email alerts
|

Bionic effects of nano hydroxyapatite dentifrice on demineralised surface of enamel post orthodontic debonding: in-vivo split mouth study

Abstract: Background Orthodontic debonding procedure produces inevitable enamel surface alterations, sequelae to which are enamel demineralization, sensitivity and retention of pigments. Several agents have been employed to counterbalance the same. The purpose of this study was (1) To evaluate the hypothesis that no significant difference exists in the remineralising potential of nano hydroxyapatite (NanoHAP) dentifrice and fluoridated dentifrice after orthodontic debonding, (2) To estimate the enamel to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…Conversely, biomimetic hydroxyapatite even leads to a mineral deposition, thus forming a real coating on enamel and dental surfaces (Lelli et al, 2014) together with composite resins (Butera, Pascadopoli, et al, 2021). Hydroxyapatite toothpastes have been shown superior remineralizing effect to fluoridated toothpastes, in post orthodontic debonding patients (Verma & Muthuswamy, 2021). Furthermore, fluoride may be linked to a risk of toxicity in case of high dosage intake, with fluorosis in children and bone diseases in the elderly (Pajor et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, biomimetic hydroxyapatite even leads to a mineral deposition, thus forming a real coating on enamel and dental surfaces (Lelli et al, 2014) together with composite resins (Butera, Pascadopoli, et al, 2021). Hydroxyapatite toothpastes have been shown superior remineralizing effect to fluoridated toothpastes, in post orthodontic debonding patients (Verma & Muthuswamy, 2021). Furthermore, fluoride may be linked to a risk of toxicity in case of high dosage intake, with fluorosis in children and bone diseases in the elderly (Pajor et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that synthetic hydroxyapatite crystals efficiently bind to enamel, acting as fillers of small defects and depression sites [ 11 , 17 ]. Furthermore, it was concluded that the bionic effect of nano-hydroxyapatite particles transmits to processes that mimic early enamel mineralization, due to increased concentrations of calcium and phosphate ions [ 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human extracted premolars were the most frequently used permanent teeth in vitro, with only two studies utilizing human incisors [26,27]. While one in vitro study [5] assessed the effects of nHAp alone, the remaining studies compared the effects of nHAp alone to those of other components such as 20% zinc carbonate nHAp, 0.14 wt percent amine fluoride, 5% NovaMin (bioactive glass), and 8% Proargin. Various concentrations of nHAp were utilized in the in vitro investigations, ranging from 1% [28] to 20% [29,30].…”
Section: Characteristics Of the Included In Vitro Studiesmentioning
confidence: 99%
“…Dental caries damage the surface of teeth and progress through stages of demineralization and remineralization before invading deeper levels of tooth lesions [4]. Similarly, during orthodontic bonding and debonding, an uneven enamel surface with micro-damage and white spot lesions is frequently observed [5], which also contributes to the likelihood of demineralization [6]. A gradual decrease in prismatic mineral content (critical layer) is the hallmark of the early stage of enamel demineralization [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation